2015
DOI: 10.1021/cs5019524
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Temperature and Size-Controlled Activation of Ruthenium-Catalyzed Ammonia Borane Hydrolysis

Abstract: Metal-catalyzed hydrolysis is an important reaction for releasing hydrogen stored in ammonia borane, a promising fuel form for the future hydrogen economy, under ambient conditions. A variety of catalysts made of different transition metals have been investigated to improve the efficiency of hydrogen generation; however, little attention has been given to the possible influence of the compensation effect on catalyst design. Using face-centered cubic (FCC) packed ruthenium (Ru) nanoparticles supported on layere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 94 publications
(260 reference statements)
6
86
0
Order By: Relevance
“…Different from Co-containing LDH in which cobalt is incorporated in the brucite layers by replacing magnesium, anion-coordinated palladium cations are intercalated between the brucite layers[80,81], which may interfere with the phase transformation process. Palladium nanoparticles can be attached on LDH or LDO surfaces by adsorption with or without the use of polymer linkers; however, this methodof direct decoration is unlikely to result in an improvement of reactivity compared to well-dispersed dendrimerstabilized palladium nanoparticles because the nanoparticles created by the direct decoration method can only create loosely attached nanoparticles[70] that can still fall off the support and aggregate.…”
mentioning
confidence: 99%
“…Different from Co-containing LDH in which cobalt is incorporated in the brucite layers by replacing magnesium, anion-coordinated palladium cations are intercalated between the brucite layers[80,81], which may interfere with the phase transformation process. Palladium nanoparticles can be attached on LDH or LDO surfaces by adsorption with or without the use of polymer linkers; however, this methodof direct decoration is unlikely to result in an improvement of reactivity compared to well-dispersed dendrimerstabilized palladium nanoparticles because the nanoparticles created by the direct decoration method can only create loosely attached nanoparticles[70] that can still fall off the support and aggregate.…”
mentioning
confidence: 99%
“…XPS analysis also demonstrated that the surface molar composition of Co-Ni-B was Co 47. 5 [6], which indicates that PAC was successfully doped into the Co-Ni-B catalyst. Figure 4c shows the high-resolution XPS spectrum of Co 2p; the peaks at 780.1 and 795.8 eV correspond to Co 2p3/2 and Co 2p1/2, respectively.…”
Section: Characterization Of the Catalystsmentioning
confidence: 90%
“…The XPS results confirm the presence of Ni, Co, B, C, N, and O in the Co-Ni-B/PAC composite. The binding energy at 398.8 eV was attributed to uncharged pyrrolic nitrogen ( Figure 4b) [6], which indicates that PAC was successfully doped into the Co-Ni-B catalyst. Figure 4c shows the high-resolution XPS spectrum of Co 2p; the peaks at 780.1 and 795.8 eV correspond to Co 2p3/2 and Co 2p1/2, respectively.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
See 2 more Smart Citations